Teaching Subject, A : Composition Since 1966, New Edition - Harris, Joseph (Joseph D.) (Book collections on Project MUSE., 2012)
"Reviewing the last 50 years of the development of writing studies as a discipline through five key ideas, Harris unfolds a set of issues and tensions that continue to shape the teaching of writing today"-- Provided by publisher.